THE REMITTANCE PARADIGM: IMPLICATIONS OF INDONESIAN MIGRANT WORKERS FOR POVERTY ALLEVIATION - Abdul Rouf; Deden Dinar Iskandar; Purbayu Budi Santosa; Wahyu Widodo (Publikasi Inspirasi Indonesia, 2026)
This study examines the relationship between the spatial distribution of the banking system, internal migration patterns, domestic remittance flows, and the level of financial inclusion in Indonesia. Spatial inequality in access to formal financial institutions remains a fundamental problem for inclusive economic development. Based on World Bank data (2024), the number of commercial bank branches in Indonesia is only around 11.69 units per 100,000 adults, indicating the limited reach of banking services in non-urban areas (World Bank, 2024). Meanwhile, the level of account ownership in Indonesia has increased to 83% in 2023, a significant increase compared to 48% in 2011 (World Economic Forum, 2025). In the external context, Bank Indonesia (2024) reported that the value of remittances from Indonesian migrant workers reached US 9.95 billion in 2023, a 3.6% increase from the previous year. These remittance flows have great potential to expand the savings base, strengthen monetary stability, and support the expansion of financial inclusion (Canales et al., 2023; Inoue & Hamori, 2016). However, this potential has not been fully realized due to spatial disparities and financial literacy gaps between urban and rural areas. The methodology used is multilevel logistic regression with microdata from the Indonesia Family Life Survey (IFLS, 2021) and macrodata from Bank Indonesia (2023), the Financial Services Authority (2024), and the Central Statistics Agency (2024). This model allows for testing hierarchical and spatial relationships between individual, household, and provincial levels. The main variables include financial inclusion (formal account ownership), internal migration status, remittance receipts, and bank branch density per km² as a proxy for geospatial access to the banking system. The results of the study show that spatial access to the banking system has a positive and significant effect on financial inclusion (Beck, Demirgüç-Kunt, & Levine, 2023). Additionally, internal migration and remittance receipts also strengthen the probability of individuals using formal financial services, indicating the existence of spatial interactions (spillover) between regions. Provinces with higher bank network density tend to transmit positive effects on financial inclusion in surrounding provinces (Krugman, 1991). These findings emphasize the importance of a geospatial approach in formulating national financial inclusion policies. Equal distribution of banking networks, strengthening financial literacy for migrants and remittance recipients, and integrating spatial data between financial institutions are key strategies for promoting more inclusive and equitable economic growth between regions.